BRAZILIAN SOCIAL SECURITY: AN ANALYSIS OF THE MUNICIPALITY OF VITÓRIA-ES’S OWN PENSION SYSTEM (REMUNOM, 2025)
This article presents an in-depth analysis of Brazilian Social Security, focusing on the Municipal Pension Scheme of Vitória, Espírito Santo (IPAMV). Inspired by our thesis for the Economics degree at UFES, with the same title, the study seeks to understand the structural challenges that compromise the system's sustainability. From a historical and institutional perspective, it highlights the relevance of the reforms implemented and the role of governance in strengthening the system. The research highlights demographic problems and the changing composition of employment relationships, which have reduced the contributory base and increased pension expenditures, putting pressure on municipal finances. It demonstrates that the sustainability of IPAMV depends on the coordination of personnel policies, actuarial balance, and fiscal discipline, revealing that the problems faced are structural in nature and require equally structural solutions to ensure lasting social protection for public servants.